Optimizacijski model poslovnega sistema kot metodološka podlaga uravnoteženemu sistemu kazalnikov poslovanja - Devjak, Srečko (Uporabna informatika (Ljubljana), 2002)
In the development of the system of indicators, we often cannot or do not knowhow to sufficiently take into account the elements of the notion "system".The use of indicators has, ecpecially with regard to the needs of the decision-making a special advantage when the indicators form a system.
Keywords: kazalniki; matematični modeli; optimizacija; poslovni sistemi; razžagovanje hlodovine